1999
DOI: 10.1292/jvms.61.1323
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Oligodendroglioma with Diffuse Arachnoidal Dissemination in a Japanese Black Heifer.

Abstract: ABSTRACT. A gelatinous focus with cystic spaces, was found in the posterior funiculus of the 2nd to 3rd lumbar levels of the spinal cord of a Japanese Black heifer, 2 years old, with clinical signs of severe dysstasia. Histopathological examination revealed that the spinal lesion consisted of multifocal and diffuse proliferation of round cells with abundant vacuolar cytoplasm and hyperchromatic nuclei. In the lesions there was a number of cystic spaces containing aggregates of small round cells. The neoplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The main differential diagnosis that needs to be considered, particularly in a tumour with intraventricular growth is the central neurocytoma, but this rare tumour has so far only been identified in humans. This tumour of neuroectodermal origin has been reported in a French bull dog, a cat, and a Japanese black heifer 1,5,9 . It seems that clinical signs are mostly due to the space-occupying effect of the tumour 3 .…”
Section: Resultsmentioning
confidence: 81%
“…The main differential diagnosis that needs to be considered, particularly in a tumour with intraventricular growth is the central neurocytoma, but this rare tumour has so far only been identified in humans. This tumour of neuroectodermal origin has been reported in a French bull dog, a cat, and a Japanese black heifer 1,5,9 . It seems that clinical signs are mostly due to the space-occupying effect of the tumour 3 .…”
Section: Resultsmentioning
confidence: 81%
“…6 Although some tumor cells have expressed these markers, their expression is not specific for oligodendrogliomas, and, thus, it appears that there are no specific markers for the detection of neoplastic oligodendrocytes. 12 In the sections examined for MBP, the myelin sheathes were well detected, but, the cell bodies of normal oligodendrocytes, which were less frequently encountered, showed faint positive immunoreactivity for MBP in a portion of cells that morphologically resembled oligodendrocytes. Recently, it was reported that some brain tumors, including astrocytoma, ependymoma, and central neurocytoma, can occasionally exhibit a honeycomb-like appearance.…”
mentioning
confidence: 88%
“…Interestingly, 2 of 3 previously reported oligodendrogliomas in cattle occurred in young adult cows and featured a similarly prominent leptomeningeal infiltration without clear primary mass, similar to the case presented here. 7,18 Altogether, these reports may suggest that bovine oligodendroglial tumors have a strong preference to develop and grow contiguously in the subarachnoid space, which might be associated with specific yet unknown mutations or neuroectodermal progenitor cell heterotopies. 11…”
mentioning
confidence: 98%
“…16 In other animals, gliomas occur sporadically. In cattle, glial tumors are considered to be rare among nervous system tumors, 4 with only 3 oligodendroglioma cases reported to date: 2 intraspinal 2,18 and 1 intracranial. 7 In general, oligodendrogliomas grow as soft to gelatinous, infiltrative but fairly demarcated intraparenchymal masses frequently invading the meninges and/or ventricles and further spreading via the cerebrospinal fluid (CSF).…”
mentioning
confidence: 99%